American Sign Language for kids : 101 easy signs for nonverbal communication - Barlow, Rochelle (Rockridge Press, 2022)
The easy way for kids (and parents) to learn American Sign Language. There has never been a better way to start learning American Sign Language. Ideal for parents of nonverbal children or children with communication impairments (ages 3-6), American Sign Language for Kids offers a simple way to introduce both of you to ASL. Build your vocabularies with 101 signs perfect for everyday use, all featuring detailed illustrations, memory tips, and hands-on activities. American Sign Language for Kids helps you focus on the types of words you need most with chapters conveniently divided by category. Get chatty with activities that guide you through conversations. You'll be signing together in no time!